Characterization of immortalized MARCO and SR-AI/II-deficient murine alveolar macrophage cell lines - Imrich Amy; Zhou Hongwei; Kobzik Lester (Particle and Fibre Toxicology, 2008)
Abstract Background Alveolar macrophages (AM) avidly bind and ingest unopsonized inhaled particles and bacteria through class A scavenger receptors (SRAs) MARCO and SR-AI/II. Studies to characterize the function of these SRAs have used AMs from MARCO or SR-AI/II null mice, but this approach is limited by the relatively low yield of AMs. Moreover, studies using both MARCO and SR-AI/II-deficient (MS-/-) mice have not been reported yet. Hence, we sought to develop continuous cell lines from primary alveolar macrophages from MS-/- mice. Results We used in vitro infection of the primary AMs with the J2 retrovirus carrying the v-raf and v-myc oncogenes. Following initial isolation in media supplemented with murine macrophage colony-stimulating factor (M-CSF), we subcloned three AM cell lines, designated ZK-1, ZK-2 and ZK-6. These cell lines grow well in RPMI-1640-10% FBS in the absence of M-CSF. These adherent but trypsin-sensitive cell lines have a doubling time of approximately 14 hours, exhibit typical macrophage morphology, and express macrophage-associated cell surface Mac-1 (CD11b) and F4/80 antigens. The cell lines show robust Fc-receptor dependent phagocytosis of opsonized red blood cells. Similar to freshly isolated AMs from MS-/- mice, the cell lines exhibit decreased phagocytosis of unopsonized titanium dioxide (TiO2), fluorescent latex beads and bacteria (Staphylococcus aureus) compared with the primary AMs from wild type (WT) C57BL/6 mice. Conclusion Our results indicated that three contiguous murine alveolar macrophage cell lines with MS-/- (ZK1, ZK2 and ZK6) were established successfully. These cell lines demonstrated macrophage morphology and functional activity. Interestingly, similar to freshly isolated AMs from MS-/- mice, the cell lines have a reduced, but not absent, ability to bind and ingest particles, with an altered pattern of blockade by scavenger receptor inhibitors. These cell lines will facilitate in vitro studies to further define MARCO and SR-AI/II function, and may also be useful to identify other novel scavenger-type macrophage receptors and for additional studies of particle toxicology.